Discovering the antibacterial mode of action of 3‐p‐trans‐coumaroyl‐2‐hydroxyquinic acid, a natural phenolic compound, against Staphylococcus aureus through an integrated transcriptomic and proteomic approach. Issue 1 (23rd September 2020) - Liu, Xiaoyan; Yue, Yuxi; Wu, Yanping; Zhong, Kai; Bu, Qian; Gao, Hong
Abstract: A plant‐derived phenolic compound, namely 3‐ p ‐ trans ‐coumaroyl‐2‐hydroxyquinic acid (CHQA), has recently been reported to exhibit antibacterial and antibiofilm activities against Staphylococcus aureus . In this study, the combined transcriptomic and proteomic analyses was used to elucidate the molecular mechanism of CHQA against S . aureus . The results showed that subinhibitory concentration of CHQA induced wide and significant changes in S . aureus at both transcriptional and translational levels with 935 differentially expressed genes and 438 differentially expressed proteins. Bioinformatic analysis indicated that the changed genes and proteins were mainly involved in cell membrane, ribosome and translation, DNA repair, fatty acid biosynthesis and metabolism, amino acid biosynthesis, peptidoglycan synthesis, and bacterial infection. Moreover, downregulation of various surface proteins associated with cell adhesion was observed, which probably further inhibited the biofilm formation of S . aureus . These results revealed that CHQA exerted antibacterial activity through multifarious mechanisms, which especially targeted bacterial cell membrane and then triggered diverse cellular dysfunctions. Abstract :